2015
DOI: 10.1038/ncomms9200
|View full text |Cite
|
Sign up to set email alerts
|

Activity-regulated trafficking of the palmitoyl-acyl transferase DHHC5

Abstract: Synaptic plasticity is mediated by the dynamic localization of proteins to and from synapses. This is controlled, in part, through activity-induced palmitoylation of synaptic proteins. Here we report that the ability of the palmitoyl-acyl transferase, DHHC5, to palmitoylate substrates in an activity-dependent manner is dependent on changes in its subcellular localization. Under basal conditions, DHHC5 is bound to PSD-95 and Fyn kinase, and is stabilized at the synaptic membrane through Fyn-mediated phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
197
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(216 citation statements)
references
References 67 publications
(181 reference statements)
18
197
0
1
Order By: Relevance
“…However, we found that steady state palmitoylation of PSD-95 was unaffected in GODZ KO mice, which is consistent with convincing evidence that PSD-95 palmitoylation is mainly mediated by DHHC2 (13), DHHC5 (34), and DHHC8 (35). In the case of AMPA receptors, overexpression of GODZ was previously reported to limit the receptor cell surface expression in cultured neurons (19).…”
Section: Discussionsupporting
confidence: 78%
“…However, we found that steady state palmitoylation of PSD-95 was unaffected in GODZ KO mice, which is consistent with convincing evidence that PSD-95 palmitoylation is mainly mediated by DHHC2 (13), DHHC5 (34), and DHHC8 (35). In the case of AMPA receptors, overexpression of GODZ was previously reported to limit the receptor cell surface expression in cultured neurons (19).…”
Section: Discussionsupporting
confidence: 78%
“…Fyn phosphorylates DHHC5 at a specific residue (Tyr533) which, like the Tyr1472 site on GluN2B, forms part of a clathrin-dependent internalization motif (Brigidi et al, 2015). Again, phosphorylation by Fyn appears to mask this motif, because Tyr533 phosphorylation promotes DHHC5 plasma membrane localization in non-neuronal cells and increases DHHC5 stability on the plasma membrane of neuronal dendritic spines (Brigidi et al, 2015). In an elegant series of experiments, Bamji and colleagues further showed that DHHC5 stability in spines involves a tri-partite complex of Fyn, DHHC5 and PSD-95 (Brigidi et al, 2015).…”
Section: Synaptic Regulation By the Palmitoylated Sfk Fynmentioning
confidence: 99%
“…Again, phosphorylation by Fyn appears to mask this motif, because Tyr533 phosphorylation promotes DHHC5 plasma membrane localization in non-neuronal cells and increases DHHC5 stability on the plasma membrane of neuronal dendritic spines (Brigidi et al, 2015). In an elegant series of experiments, Bamji and colleagues further showed that DHHC5 stability in spines involves a tri-partite complex of Fyn, DHHC5 and PSD-95 (Brigidi et al, 2015). Interestingly, this complex can be rapidly regulated by changes in neuronal activity, with important consequences for synaptic transmission and plasticity.…”
Section: Synaptic Regulation By the Palmitoylated Sfk Fynmentioning
confidence: 99%
“…37 PDZ-mediated interactions between DHHC5 and neuronal PSD-95 protein was previously shown 38 and, in a separate study, a mutant of DHHC5 with a deletion of the PDZ domain (DHHC5 ÁPDZb) could not bind to PSD-95. 39 Moreover, SH3 domain and SH3-binding domain interactions between selenoprotein K (Selk) and DHHC6 were reported to be required for palmitoylation of the Ca 2þ channel protein, inositol 1,4,5-triphosphate (IP3) receptor: IP3R. 40 On the other hand, the protein interaction/recognition domains of DHHC proteins might play roles separate to substrate recognition as, for example, in the case of the Cterminal residues of DHHC5, which were shown to be involved in the interaction with the SH3 domain of Fyn, a member of the Src-family of kinases.…”
Section: Zdhhc Proteins: Substrate-specificitymentioning
confidence: 99%
“…Mutation of the most critical prolines that lie within this sequence resulted in a protein that was unable to bind to the SH3 domain of Fyn which, in turn, blocked the Fyn-mediated phosphorylation of DHHC5, thus enhancing the dissociation of DHHC5 from the membrane. 39 Mention should also be made of the study that argues against any specific DHHC-substrate interactions, stating that, in order for a protein to be palmitoylated, it only needs to have an accessible cysteine residue that can transiently locate at Golgi membranes; the basic site in the cell where PATs reside. 24 Thus, further studies are needed to finally resolve the issue of PAT substrate-specificity.…”
Section: Zdhhc Proteins: Substrate-specificitymentioning
confidence: 99%